1989
DOI: 10.1254/jjp.51.211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bifemelane hydrochloride on various cholinergic markers in cortical and subcortical regions of aged rats.

Abstract: Abstract-The effects of bifemelane hydrochloride (BF) upon various cholinergic markers, muscarinic receptors, acetylcholinesterase (AChE) and choline acetyl transferase (CAT), in the aged rat brain were examined. Marked reduction of the density of muscarinic receptors (BmaX) as well as AChE and CAT activity con comitant with aging was observed. Administration of BF in daily doses of 10 mg/ kg for 4 weeks to aged rats significantly decreased the apparent dissociation constant (Ku) for QNB in muscarinic receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Because it is well-known that the functioning cholinergic system can be damaged by cerebral ischemia (14), we compared various cholinergic biochemical markers (mAChR and ChAT activity) in the cortex, hippocampus and striatum of the brains of aged (24 month) and young (6 weeks) rats treated with permanent 2VO. We previously reported that the investigation of brain cholinergic systems in aged control rats could provide useful information pertaining to age and age-related disorders in humans (9,10). However, in this study, ChAT activity and the number of mAChR in aged 2VO rats decreased nearly 10-20% as compared with those in aged control rats.…”
Section: Choline Acetyltransferase Activity Assaycontrasting
confidence: 60%
See 1 more Smart Citation
“…Because it is well-known that the functioning cholinergic system can be damaged by cerebral ischemia (14), we compared various cholinergic biochemical markers (mAChR and ChAT activity) in the cortex, hippocampus and striatum of the brains of aged (24 month) and young (6 weeks) rats treated with permanent 2VO. We previously reported that the investigation of brain cholinergic systems in aged control rats could provide useful information pertaining to age and age-related disorders in humans (9,10). However, in this study, ChAT activity and the number of mAChR in aged 2VO rats decreased nearly 10-20% as compared with those in aged control rats.…”
Section: Choline Acetyltransferase Activity Assaycontrasting
confidence: 60%
“…We these data should aid in establishing a model of senile also investigated the effect of long-term administration dementia that could be used to investigate potentially of bifemelane on cholinergic markers in aged 2VO rats; therapeutic drugs (9,10). This model, however, employbifemelane is known to be an effective treatment for ed rats that were simply aged, not true models of senile cerebrovascular disease in clinical trials as well as in dementia.…”
mentioning
confidence: 99%